Implikasi Humanisme Antroposentris dalam Kehidupan Manusia Modern - Saputri, Ayu Aprilina; Nasution, Fadia Putri (JURNAL AL-AQIDAH, 2024)
Humanism is a school of thought that emphasizes human value and dignity, individual freedom, and the potential for human rationality in shaping their own lives. This research was conducted using qualitative research with a descriptive approach. Humanism developed from Renaissance thought which shifted attention from cosmocentrism and theocentrism to anthropocentrism, where humans became the center of thought. However, humanism is not free from criticism, especially from the perspective of religion, postmodern philosophy, and ecology which considers humanism to be too human-centered and ignores divine and environmental aspects. In this research, humanism is discussed in relation to divinity, criticism of humanism, and its implications in various aspects of life, such as education, psychology, philosophy, and art. This descriptive qualitative research was carried out through data analysis from various literary sources, revealing that despite criticism, humanism has had a significant influence on the development of human rights, democracy, and rational and secular thinking in the modern world.